Il libro dello spreco. Sullo stile tardo di Italo Calvino (ENTHYMEMA, 2020)
In 1967 Italo Calvino moved to Paris and programmatically decided to enter into his old age. This choice also influences the style of his following narrative production. In this perspective, my essay faces the novel If on a Winter’s Night a Traveler looking at the notion of late style coined by Theodor W. Adorno, which assumes the closeness of the death to the author as the cause of a divergence between artistic conventions and his subjectivity. I will try to show how the formal waste of the selfless virtuosic novel actually reflects its author’s ethics of difficulty. According to Calvino everything, men and books, needs to be justified by a project that implies «voluntary choices» and «active renunciations».
Keywords: Italo Calvino; If on a Winter’s Night a Traveler; Theodor W. Adorno; late style; literature as project